2015
DOI: 10.1002/nau.22732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the phosphodiesterase 5 inhibitor Tadalafil on bladder function in a rat model of partial bladder outlet obstruction

Abstract: Tadalafil suppressed the reduction in bladder blood flow caused by BOO in rats and improved urinary function. This action of Tadalafil may contribute to its amelioration of bladder function. Neurourol. Urodynam. 35:444-449, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
(47 reference statements)
1
30
0
Order By: Relevance
“…We suspended tadalafil in a 0.5% methylcellulose solution, using an agate mortar and pestle, to create a 2 mg/mL solution; the drug was administered (1 mL/kg body weight) according to a previous tadalafil report . Six weeks after inducing diabetes, rats in the DT group received oral tadalafil (2 mg/kg/day) daily for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…We suspended tadalafil in a 0.5% methylcellulose solution, using an agate mortar and pestle, to create a 2 mg/mL solution; the drug was administered (1 mL/kg body weight) according to a previous tadalafil report . Six weeks after inducing diabetes, rats in the DT group received oral tadalafil (2 mg/kg/day) daily for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Given that the expression of PDE5 mRNA is observed in both iliac and vesical arteries, previous reports have shown that chronic treatment with tadalafil increased BBF by inhibiting PDE5. 19,20 Furthermore, chronic treatment with 2 mg/kg tadalafil improved bladder dysfunction in the chronic bladder ischemic rat model. 6 Kawai et al reported that chronic treatment with 10 mg/kg tadalafil ameliorated bladder dysfunction in the bladder outlet obstruction rat model.…”
Section: Discussionmentioning
confidence: 94%
“…The major artery that supplies blood to the rat bladder is the vesical artery, a branch of the internal iliac artery. Given that the expression of PDE5 mRNA is observed in both iliac and vesical arteries, previous reports have shown that chronic treatment with tadalafil increased BBF by inhibiting PDE5 . Furthermore, chronic treatment with 2 mg/kg tadalafil improved bladder dysfunction in the chronic bladder ischemic rat model .…”
Section: Discussionmentioning
confidence: 95%
“…Tadalafil was suspended in 0.5% methylcellulose solution using an agate mortar and pestle to obtain a 2 mg/mL solution. Rats were administered tadalafil (1 mL/kg body weight) according to a previous report . Briefly, tadalafil (2 mg/kg/d) was administered orally to rats in the DT group for 7 days from Week 6 to Week 7 after the induction of diabetes.…”
Section: Methodsmentioning
confidence: 99%